Pelvic floor dysfunction in female Sjögren's syndrome: an 8-year audit. Issue 9 (September 2016) - Budden, Aaron; West, Nèvine; Sturgess, Allan; Moore, Kate
Abstract Introduction and hypothesis The classic triad of dry eyes, mouth and vagina is known to most gynaecologists as pathognomonic of Sjögren's syndrome, but rheumatologists seldom consider vaginal symptoms. Our hypothesis was that women with Sjögren's syndrome would have an increased likelihood of postoperative voiding dysfunction, severe vaginal stenosis or poor response to anticholinergics compared with the general urogynaecology patient. Methods All patients with Sjögren's syndrome were prospectively recorded from July 2007 to June 2015. Presenting complaint, pelvic examination findings, previous/subsequent pelvic surgery, voiding dysfunction and response to anticholinergics were noted. The denominator, all new urogynaecology patients, was prospectively recorded. Results Fifteen patients were identified over 8 years (0.5 % of 2794 new presentations). Of the seven patients who had previously undergone surgery elsewhere, all had demonstrable pelvic tissue fibrosis; five had such severe fibrosis that no speculum could be passed. Anticholinergic medications were completely intolerable in 10/11 (91 %) women, and severe postoperative voiding dysfunction occurred in 6/9 (67 %) women. Only 2/15 (13 %) women were unaffected by fibrosis, postoperative voiding dysfunction or intolerance to anticholinergics. Conclusions This audit demonstrates a substantial risk of vaginal stenosis, postoperative voiding dysfunction or severe intolerance to anticholinergics in women with Sjögren's syndrome.